Caracterização de Sistemas Binários Eclipsantes da Missão CoRoT - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
In this paper, we analyze 28 eclipsing binary systems observed during the CoRoT mis- sion. The campaign, which began in 2007 and ended in 2011, allowed the observation of these systems in the region of the center and anticenter of the galaxy, including stars with magni- tudes from 6 to 16. Our aim was to remove the systematic effects present in the light curves and to calculate the orbital periods and initial epochs of all the targets. In addition, we modeled the light curves of the detached system CoRoT ID 0651331676 and the supercontact systems CoRoT ID 0310144545, CoRoT ID 0223934244 and CoRoT ID 0224009552 to obtain the fol- lowing physical parameters: mass ratio, orbital inclination, temperature of the primary star and potential of both components. We used an algorithm called Periodic Detrend, written in Python, which was developed by a researcher in our research group. With this algorithm, we removed the component of the signal coming from systematic effects from the light curve and calculated the orbital period of all the objects. The light curves were modeled using the Wilson-Devinney algorithm implemented in conjunction with the emcee package of the Python programming language to obtain the probability distribution of the parameters and their respective errors. Of the targets analyzed, 85.7% correspond to the supercontact classification, with periods of less than 1.2 days. The CoRoT target ID 0651331676 is the only one detached, with a period of 3.5836 ± 0.0002 days.
Keywords: Estrelas Binárias; Wilson-Devinney; Periodic Detrend; CoRoT; Binary Stars; Wilson-Devinney; Periodic Detrend; CoRoT; CNPQ::CIENCIAS EXATAS E DA TERRA